IMPACT OF BUSINESS MODELS CANVAS LEARNING ON IMPROVING LEARNING ACHIEVEMENT AND ENTREPRENEURIAL INTENTION - Hutasuhut, Saidun; Irwansyah, Irwansyah; Rahmadsyah, Agus; Aditia, Reza (Jurnal Cakrawala Pendidikan, 2020)
Indonesian university graduates skills in creating job opportunities or entering the workforce are still low. It can be seen from the facts that the undergraduate unemployment rate is still higher than the national unemployment rate. Although entrepreneurship education has been considered as one solution to this problem, the best entrepreneurship education model has not been agreed among researchers. This study examines the application of Business Model Canvas (BMC) on enhancing student achievement and student entrepreneurial intentions and the interaction of entrepreneurial learning achievement levels and the application of BMC on entrepreneurial intentions. The method used in this research is quasi-experiment by assigning two classes of entrepreneurship courses at the Faculty of Economics, Medan State University, one class as an experimental class (BMC) and the other class as the control class. Hypothesis testing was conducted with t-test and ANOVA. The findings showed that the average entrepreneurial learning achievement of the BMC class was 12.52% higher than that of the control class. Entrepreneurial intentions of the BMC class was only 6.15% higher than that of the control class. BMC is proven to be positive and significantly improves learning achievement. The level of learning achievement is proven to be positive and it significantly increases entrepreneurial intentions. However, BMC learning has not been proven to increase entrepreneurial intentions. The results of this study are useful for entrepreneurial instructors to design learning that can increase entrepreneurial intentions.